Differentially expressed microRNAs in pre-transplant lung biopsies target immune checkpoint proteins and can predict primary graft dysfunction in lung transplantation - Vitale Miceli; Pia Ferrigno; Claudio Centi; Claudia Carcione; Gioacchin Iannolo; Valentina Agnese; Giovanna Lo Iacono; Rosa Liotta; Pier Giulio Conaldi; Massimo Pinzani; Lavinia De Monte; Alessandro Bertani (Heliyon)
Lung transplantation (LTx) significantly improves outcomes for patients with end-stage respiratory failure. However, primary graft dysfunction (PGD) remains one of the most relevant hurdles. Although PGD is attributed to ischemia-reperfusion injury (IRI), immune responses, primarily T cell-mediated, may play a pivotal role in its pathogenesis. Additionally, innate immune activation following IRI links PGD to adaptive alloimmunity, highlighting the impact of early events on LTx outcomes. Immune checkpoints (ICPs) such as PD-1/PD-L1, CD40/CD40LG, and OX40/OX40L, regulate post-LTx T cell responses, and dysregulation of microRNAs (miRNAs) has been implicated in altering ICP expression, influencing the amplification of immune responses.In this preliminary study, we used the taqMan low-density array (TLDA) cards to investigate miRNA dysregulation's prognostic potential as a PGD marker in pre-transplant back-table lung biopsies. Our analysis revealed differential miRNA expression in donor lung tissues, potentially associated with PGD onset, targeting immune regulatory pathways. Specifically, deregulated miRNAs targeted key ICP proteins, including PD-L1, CD40LG, and OX40L. Moreover, the differential expression of these miRNAs was observed in grafts with future PGD compared to grafts without PGD, suggesting a potential prognostic benefit and a possible role for lung tissue miRNAs in the onset of early graft dysfunction.These findings provide a basis for future investigations into their mechanistic roles and therapeutic potential for PGD. Although based on a limited number of cases, our results imply that miRNAs might be involved in early graft dysfunction. While requiring validation in larger cohorts, our data raise the possibility that the evaluation of the aforementioned markers during the pre-transplant phase, might offer a prognostic benefit in monitoring the onset of PGD. Additionally, the use of compounds that can modulate the function of these molecules could be evaluated for the management of LTx patients.